1995
DOI: 10.1111/j.1460-9568.1995.tb01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch‐clamp Analysis of Synaptic Transmission to Cerebellar Purkinje Cells of Prion Protein Knockout Mice

Abstract: The prion protein (PrP) plays a pivotal role in transmissible spongiform encephalopathies such as Creutzfeldt-Jakob disease in humans and scrapie and bovine spongiform encephalopathy in animals. Previous experiments have suggested that the normal cellular prion protein (PrPc) is involved in synaptic function in the hippocampus. Here, we utilized the controlled recording conditions of the patch-clamp technique to investigate the synaptic function of prion protein in cerebellar Purkinje cells. By performing whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
3
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 28 publications
3
37
3
1
Order By: Relevance
“…In particular, they agree with results showing that synaptic transmission in cerebellar Purkinje cells and at the neuromuscular junction is normal in Prnp0/0 mice (26,27). However, they are in striking contrast to recent results, in which changes in GABAA receptor-mediated inhibition and LTP were reported in CAl hippocampal pyramidal cells (12)(13)(14).…”
Section: Methodscontrasting
confidence: 57%
“…In particular, they agree with results showing that synaptic transmission in cerebellar Purkinje cells and at the neuromuscular junction is normal in Prnp0/0 mice (26,27). However, they are in striking contrast to recent results, in which changes in GABAA receptor-mediated inhibition and LTP were reported in CAl hippocampal pyramidal cells (12)(13)(14).…”
Section: Methodscontrasting
confidence: 57%
“…The reason why, in adult PrP 0/0 mice, behavioral tests appeared normal (Bü eler et al, 1992;Herms et al, 1995;Lipp et al, 1998), is probably because slow-spiking granule cells eventually recover a normal fastspiking phenotype and synaptic plasticity. The potential impact of the temporary disruption of the cerebellar circuit during a time window critical for sensorimotor development (Altman and Sudarshan, 1975) remains to be determined, but it may have a reflection in some of the late motor, cognitive, and emotional abnormalities of PrP 0/0 mice (Roesler et al, 1999;Walz et al, 2002;Criado et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Because it was reported that motor performance in adult PrP 0/0 mice was normal (Bü eler et al, 1992;Herms et al, 1995;Lipp et al, 1998), an obvious question was whether the alterations at the mossy fiber-granule cell relay of juvenile PrP 0/0 mice disappeared with adulthood. We therefore repeated the critical measurements on PrP 0/0 mice at P40 -P50 (Fig.…”
Section: Alterations At the Mossy Fiber-granule Cell Relay Disappear mentioning
confidence: 99%
“…However, it was finally demonstrated that Edimburgh Prnp-knockout mice show alterations in circadian rhythms (Tobler et al, 1996) and cognitive deficits (Criado et al, 2005). In addition, both lines showed deficits in synaptic transmission (Collinge et al, 1994;Herms et al, 1995) and increased sensitivity to oxidative stress (Brown et al, 2002). Recent studies indicate that these mice also show increased susceptibility to glutamate excitotoxicity (Khosravani et al, 2008a;Rangel et al, 2007;Walz et al, 1999;Walz et al, 2002) as a result of changes in the expression of glutamate receptor subunits (Khosravani et al, 2008a;Lledo et al, 1996;Rangel et al, 2007).…”
Section: Prnp-deficient Micementioning
confidence: 99%